Internalisasi Prinsip Moderasi Beragama dalam Mewujudkan Generasi Z Islam Moderat - Syarifah, Sabilatus; Hidayat, Fahri (Al Ashriyyah, 2024)
The research explores the impact of internalizing values of religious moderation on shaping Generation Z towards practicing Wasatiyyah Islam. The research method employed is literature review, a research technique that focuses on data collection through the analysis of literature from various sources relevant to the research topic. The findings of the research indicate that religious education that encourages the internalization of values of religious moderation has a significant impact on shaping Generation Z, which tends to embrace Wasatiyyah Islam. Overall, education on religious moderation plays a crucial role, especially in the context of Indonesian society characterized by pluralism and multiculturalism. Comprehensive religious education curriculum and relevant teaching methods, aligned with the preferences of the digital-era Generation Z, play a crucial role. A profound understanding of religious moderation serves as the basis for fostering social harmony and appreciation for diversity. Education emerges as a key element in shaping a correct understanding of religion and engaging the younger generation, especially Generation Z.